Carbamazepine-Related Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
High serum carbamazepine-epoxide concentrations were correlated with unexpected seizure exacerbation and partial status epilepticus in 6 young adults reported from the Marshfield Clinic, WI, and the Mayo Clinic, MN.